The Relationship Between Fat-Free Mass and Glucose Metabolism in Children and Adolescents: A Systematic Review and Meta-Analysis - Wu, Lijun; Chen, Fangfang; Liu, Junting; Hou, Dongqing; Li, Tao; Chen, Yiren; Liao, Zijun (Frontiers in Pediatrics, 2022)
Purpose: To assess the relationship between fat-free mass (FFM) and glucose metabolism in children 0–18 years of age. Methods: We performed a systematic review of the literature on Medline/PubMed, SinoMed, Embase, and the Cochrane Library using the PRISMA 2020 guidelines to 12 October 2021; this encompassed observational studies in which the relationship between FFM and glucose metabolism was assessed. Correlation coefficient (r), regression coefficient (β), and odds ratio (OR) values in the studies were extracted and recorded as the primary data. “Agency for Healthcare Research and Quality” quality-assessment forms recommended for cross-sectional/prevalence studies were applied to evaluate the quality of the selected studies, and we executed R software to combine the pooled data. Results: We included eight studies comprising 13282 individuals, five of which involved the assessment of the relationship between FFM and blood glucose, and four on the relationship between FFM and insulin resistance (IR). Our results showed that FFM was significantly associated with fasting plasma insulin levels (r = 0.34, 95% CI: 0.30-0.39, P < 0.001). Due to high heterogeneity or insufficient quantity of data, the studies of the relationship between FFM and fasting plasma glucose, HOMA-IR, or HbA1c were not congruent, and were therefore not suitable for meta-analysis. Conclusion: Our results indicated that FFM was significantly associated with fasting plasma insulin levels. As far as we have determined, this is the first-ever systematic review and meta-analysis of the associations between FFM and glucose metabolism in children and adolescents; and our results thus provide novel information to fill a gap in the literature in this area.